Identificação de chlamydia trachomatis, mycoplasma hominis e ureaplasma urealyticum, em gestantes e não gestantes - Bastos, Carla A.; Bravo, Renato S.; Lopes, Helena R.; Figueiredo, Cláudio (Brazilian Journal of Sexually Transmitted Diseases, 2002)
Chlamydia trachomatis. Micoplasma hominis and Ureaplasma urealyticum are aetiopathological agents of endocervicitis in sexually ative women. The lack of diagnose and/or treatment may represent a huge Public Health problem and can turn into a scries of complications as:endometritis, inflamatory pelvic disease.slerelity.and neonatal infections (pulmonaries and oftalmologycals). Objectives: Our aim was to determinate the frequency of endocervicites caused by Chlamydia trachomatis, Micoplasma hominis and Ureaplasma urealyticum, in women which were attended at a prived Gynaecology and Obstetrics clinic in Ramos (Rio de Janeiro-Brasil) .and also correlates the results of their treatment with I gr of azilromicin. Paciente and Methods: A prospective study was made in sexually active women with age ranging between 15 and 49 years old. which had looked for G&O attendance, for different reasons. and hadn’t been taken medication for at least 15 days before medical appointmcnt.This study was data based on: interview. gynaecological exam with pap smear sampling and endocervical scraping specimens analized by specific methods (ELISA-SYSTEM for Chlamydia trachomatis, and Bio Merieux for Micoplasma hominis and Ureaplasma urealyticum Results: The study sample consisted of 123 patients (58 pregnants and 65 non-pregnant). Clamydia antigens were detected in 3.2% of the studied population (3.4% non-pregnants and 3% pregnants).Therefore the study sample delected a frequency of 17.8% positive patients for Ureaplasma and Mycoplasma (16.9% non-pregnants and 18.9% pregnants). Conclusion: The clinical and colpocytological findings weren’t specific enough to diagnose those genital infections.this way. routine screening of those bactcries. in sexually active women may improve the diagnostic rate and offer importants benefits for the female population.